"Be a Machine": International Graduate Students' Narratives around High-Stakes English Tests. Issue 2 (15th March 2019) - Sinclair, Jeanne; Larson, Elizabeth Jean; Rajendram, Shakina
ABSTRACT: The number of internationally mobile students pursuing higher education increases each year, with 8 million students expected to study abroad globally by 2025 (Farrugia, 2014). Many English-dominant universities require international applicants to provide standardized test scores as evidence of English proficiency. Accordingly, millions of students write tests such as the International English Language Testing System (IELTS) and the Test of English as a Foreign Language (TOEFL) each year. Much research has investigated these tests' technical properties; however, less has explored the lived experiences around these tests. The current paper responds to calls for research investigating test-takers' perspectives and contributes to research about the social and personal impact of such tests. It centers on the life stories of four Canadian-based international graduate students who took the IELTS or TOEFL. Through narrative portraiture we explore how language tests may enable and constrain these students' life choices. The paper is guided by this research question: What do successful test-takers' narratives about learning English and navigating high-stakes English tests reveal about the relationship between student agency and durable structures?